Novel bioadsorbents based on date pits for organophosphorus pesticide remediation from water. Issue 1 (February 2020) - Hassan, Siham S.; Al-Ghouti, Mohammad A.; Abu-Dieyeh, Mohammed; McKay, Gordon
Abstract: The aim of the study was to examine the efficiency of date pits as an adsorbent to remove the organophosphate pesticide (profenofos) from water. A thermodynamic study was carried out to determine the homogeneity and spontaneous nature of the adsorbents. Three types of adsorbents, namely roasted date pits, activated date pits and nano-activated date pits were prepared from the date pits. Different physical and chemical characterizations were studied such as, scanning electron microscopy (SEM), Fourier transform infrared (FTIR), Brunauer-Emmett-Teller (BET) surface area, pore radius and pore volume. The surface area of the nano-activated date pit was the highest (485.4 m 2 /g). Moreover, the pore volume and pore radius were also the highest for the nano-activated date pits with values, 0.338 cm 3 /g and 17.8 Å, respectively. Therefore, nano-activated date pits have resulted in high removal percentage and removal capacity of profenofos from aqueous solution. Based on Langmuir adsorption isotherm model, the values of R 2 was the highest for the nano-activated date pits. The adsorption maximum capacity (Qm ) increased with temperature and was maximum for the nano-activated date pit following Langmuir adsorption isotherm model. Thermodynamic parameters showed a negative ΔG o for all three adsorbents and the values increased with temperature. The ΔH o value was positive for the three adsorbents and was the highest for roasted date pit (23.59 KJ/mol); resulting in an endothermic reaction. Whereas, the value of ΔS o was negative for the three adsorbents and was the highest for nano-activated date pits (-83.5 J/mol.K).